Pengaruh Perbandingan Terigu Dan Tepung Beras Merah (Oryza nivara) Terhadap Karakteristik Kue Lumpur - Sabila, Maureen; Suter, I Ketut; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
The research aims to determine the effect of wheat flour and brown rice flour ratio to the characteristics of lumpur cake and to know the right ratio from wheat flour and brown rice flour to produce lumpur cake with the best characteristics. The Completely Randomized Design was used in this research with the treatment ratio of wheat flour and brown rice flour which consisted of six levels, such as 100% : 0%, 80% : 20%, 60% : 40%, 40% : 60%, 20% : 80%, and 0% : 100%. Each treatments was repeated 3 times so that obtain 18 experiment units. The datas were analyzed by analysis of variance and if there were some effects of the treatment, the analysis followed by Duncan's Multiple Range Test. The result showed that wheat flour and brown rice flour ratio had some effects on water content, crude fiber content, anthocyanin content, antioxidant activity and color of lumpur cake. Ratio of 0% wheat flour and 100% brown rice flour had the best characteristics, with 53.21 % water content, 7.61% crude fiber content, 20.20 mg/100g anthocyanin content, 72.27% antioxidant activity, with sensory characteristics color and aroma liked, texture, taste and overall acceptance netral. Keywords: wheat flour, brown rice flour, characteristics, lumpur cake.